Prevalence and subtype distribution of blastocystis sp. in cattle from Pahang, Malaysia - Kamaruddin, Sitie Kasmadiana; Mohammad, Mardhiah; Mat Yusof, Afzan (Malaysian Society of Parasitology and Tropical Medicine (MSPTM), 2020)
Blastocystis sp. is a common enteric protozoan parasite found in humans and various types of animals worldwide. Recently, genotypic distribution of Blastocystis sp. were revealed in insects, rodents, avian and mammals, which exposed its potential of transmiting the infection to human. However, very little information on current levels of Blastocystis sp. infection were reported in cattle from Malaysia. Herein, a total of 120 stool samples of cattles were collected. While the potential risk of infection such as age, gender, body score, diarrheic condition of the cattle were noted, and the condition as well as the management of the farms was also recorded. All stool sample were cultured, but 80 samples were selected for PCR sequencing analysis. The cultivation and microscopic examination revealed only 25% of the cattle (30/120) were infected with Blastocystis sp.. But, 43.8% of the cattle (35/80) were found positive upon PCR sequencing. The study also found that age, body score condition, diarrheic condition and certain farm were associated with the infection (p<0.05). Six subtypes (STs) that were discovered during the study were ST10 (21.3%;17/35), ST5 (8.8%;7/35), ST3 (7.5%;6/35), ST1 (2.5%;2/35), ST4 (2.5%;2/35) and ST14 (1.3%;1/35). Thus, moderate infections and variants in the genotypic distributions of the cattle suggest its potential for zoonotic transmission. Therefore, this findings could be helpful for further understanding the parasite, which assist studies of its pathogenicity.